Gatekeeping in BSW programs - Gibbs, Patty; Blakely, Eleanor H. (Columbia University Press, 2000)
Social work educators and degree program administrators face difficult issues concerning law, student rights, and social justice in their role as gatekeepers of the social work profession. How, and why, should baccalaureate social work programs afford or restrict access to the profession? When do gatekeeping strategies mask educators' reluctance to tackle some of the more thorny issues that have plagued higher education in general, for example, academe's often limited success in addressing a variety of student special needs? Balancing the interests of a diverse student population, a baccalaure.